Protein Family Content Uncovers Lineage Relationships and Bacterial Pathway Maintenance Mechanisms in DPANN Archaea - Castelle, Cindy J.; Méheust, Raphaël; Jaffe, Alexander L.; Seitz, Kiley; Gong, Xianzhe; Baker, Brett J.; Banfield, Jillian F. (Frontiers in Microbiology, 2021)
DPANN are small-celled archaea that are generally predicted to be symbionts, and in some cases are known episymbionts of other archaea. As the monophyly of the DPANN remains uncertain, we hypothesized that proteome content could reveal relationships among DPANN lineages, constrain genetic overlap with bacteria, and illustrate how organisms with hybrid bacterial and archaeal protein sets might function. We tested this hypothesis using protein family content that was defined in part using 3,197 genomes including 569 newly reconstructed genomes. Protein family content clearly separates the final set of 390 DPANN genomes from other archaea, paralleling the separation of Candidate Phyla Radiation (CPR) bacteria from all other bacteria. This separation is partly driven by hypothetical proteins, some of which may be symbiosis-related. Pacearchaeota with the most limited predicted metabolic capacities have Form II/III and III-like Rubisco, suggesting metabolisms based on scavenged nucleotides. Intriguingly, the Pacearchaeota and Woesearchaeota with the smallest genomes also tend to encode large extracellular murein-like lytic transglycosylase domain proteins that may bind and degrade components of bacterial cell walls, indicating that some might be episymbionts of bacteria. The pathway for biosynthesis of bacterial isoprenoids is widespread in Woesearchaeota genomes and is encoded in proximity to genes involved in bacterial fatty acids synthesis. Surprisingly, in some DPANN genomes we identified a pathway for synthesis of queuosine, an unusual nucleotide in tRNAs of bacteria. Other bacterial systems are predicted to be involved in protein refolding. For example, many DPANN have the complete bacterial DnaK-DnaJ-GrpE system and many Woesearchaeota and Pacearchaeota possess bacterial group I chaperones. Thus, many DPANN appear to have mechanisms to ensure efficient protein folding of both archaeal and laterally acquired bacterial proteins.